Mother’s Satisfaction with Midwifery Services at Martubung Community Health Center, Indonesia: A Cross Sectional Study - Tarigan, Yenni Gustiani; Purba, Ivan Elisabeth (Universitas Fort De Kock Bukittinggi, 2025)
Background: Mortality in women during pregnancy and childbirth still becomes a major concern in many developing countries. Almost 95% of all maternal deaths occurred in low and lower middle-income countries, and most could have been preventedPurpose: to examine the determinants of mother’s satisfaction in midwifery services at the Martubung community health center in 2022.to examine the determinants of mother’s satisfaction in midwifery services at the Martubung community health center in 2022. Methods: This was a descriptive analytic research based on a cross sectional research design. The population was 314 patients including pregnant women, postpartum mothers and infants’ mothers who visited the health center from March to June 2022; 145 mothers served as research samples, selected through random sampling technique. A standardized questionnaire was administered to collect patients’ satisfactory about midwifery service. We used demographic characteristics and the satisfaction questionnaires. Bivariate and multivariate analyses were performed in data analysis. Results: The results showed that there were significant relationships between mothers’ satisfaction and the independent variables including tangible (p-value=0.00), reliability (p-value=0.00), responsiveness (p-value=0.00), assurance (p-value=0.00), and empathy (p-value=0.00) at Martubung health center. Meanwhile, the most dominant factor was reliability (97%). Conclusion: These findings suggest the necessity of mobile health services by visiting pregnant, postpartum and neonatal women and improving the quality of maternal and child health duties by participating in midwifery training